Students' Perceptions Students' Perceptions in Using Quizizz Application in Reading Comprehension For Grade 8th Junior High School: Students' Perceptions in Using Quizizz Application - Ummi Khalsum, Juriah (Magister Pendidikan Bahasa Inggris Universitas Jambi, 2024)
Technology has positive effects on education, including active learning in the classroom, collaborative learning, creative learning, and evaluative learning. This is also helped by the expansion of information and communication technology (ICT), which offers several advantages for the development of pupils' language abilities, especially in reading. This study aims to determine the students' perceptions based on students'in using Quizizz Application in reading comprehension at SMPN 23 Tanjung Jabung Timur, Jambi province. The researcher used a quantitative research with descriptive method and employed questionnaire to collect the data. The subjects of this research are 58 students at SMPN 23 Tanjung Jabung Timur. The findings showed that most students have positive perceptions toward Quizizz as an assessment tool. They agreed that Quizizz made them have new experiences in reading comprehension in the English class because the get new information, this Quizizz has complete and flexible features is easy to use, makes students understand the reading comprehension material better. The problems met by students in using Quizizz such as students are disturbed by notifications from other applications when doing exercises through Quizizz, afraid of being constrained by an unstable network, time limits for working on questions that are displayed and according to students' perceptions, not all reading comprehension matches using Quizizz.